A Longitudinal Study of School Belonging and Academic Motivation Across High School. Issue 2 (24th September 2012) - Neel, Cari Gillen‐O'; Fuligni, Andrew
<x xml:space="preserve">Abstract</x> This longitudinal study examined how school belonging changes over the years of high school, and how it is associated with academic achievement and motivation. Students from Latin American, Asian, and European backgrounds participated (N = 572; age span = 13.94–19.15 years). In ninth grade, girls' school belonging was higher than boys'. Over the course of high school, however, girls' school belonging declined, whereas boys' remained stable. Within‐person longitudinal analyses indicated that years in which students had higher school belonging were also years in which they felt that school was more enjoyable and more useful, above and beyond their actual level of achievement. Results highlight the importance of belonging for maintaining students' academic engagement during the teenage years.